THE POWER OF IRONY IN CHARLOTTE PERKINS GILMAN’S "THE YELLOW WALLPAPER" - Shamsiyeva Sevara Ruslanovna (Galaxy International Interdisciplinary Research Journal, 2024)
In "The Yellow Wallpaper" Charlotte Perkins Gilman skillfully employs irony to criticize the oppressive treatment of women in the 19th century, especially regarding mental health. Through various forms of irony — situational, dramatic, and verbal — she highlights the devastating outcomes of a medical and societal system that disregards women's experiences. The story serves as a profound exploration of the risks of silencing women's voices and enforcing strict gender roles. By integrating irony throughout the narrative, Gilman not only enhances the reader's connection to the story but also conveys an enduring message about the necessity of autonomy, empathy, and understanding in mental health care.